2007
DOI: 10.1111/j.1468-2958.2007.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Children?s Responses to Computer-Synthesized Speech in Educational Media: Gender Consistency and Gender Similarity Effects

Abstract: This study examines children's social responses to gender cues in synthesized speech in a computer-based instruction setting. Eighty 5th-grade elementary school children were randomly assigned to one of the conditions in a full-factorial 2 (participant gender) 3 2 (voice gender) 3 2 (content gender) experiment. Results show that children apply gender-based social rules to synthesized speech. More specifically, children evaluate synthesized speech more positively, trust the speech more, and learn more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Surprisingly in light of the above, a study with university students learning probability calculation with dynamic visualizations accompanied by a male or female model's narration showed that a female model was preferred and led to better learning outcomes than a male model (Linek et al 2010). However, findings of Rodicio (2012) and Lee et al (2007) suggest the opposite, namely that male narrations should be preferred. More specifically, Rodicio (2012) found that university students learned more about geology from dynamic visualizations with a male voice-over than a female voice-over, and Lee et al (2007) found that for male students, a male computer-generated voice was more positively evaluated, trusted, and led to higher confidence levels than a female computer-generated voice.…”
Section: Model-observer Similaritymentioning
confidence: 80%
See 2 more Smart Citations
“…Surprisingly in light of the above, a study with university students learning probability calculation with dynamic visualizations accompanied by a male or female model's narration showed that a female model was preferred and led to better learning outcomes than a male model (Linek et al 2010). However, findings of Rodicio (2012) and Lee et al (2007) suggest the opposite, namely that male narrations should be preferred. More specifically, Rodicio (2012) found that university students learned more about geology from dynamic visualizations with a male voice-over than a female voice-over, and Lee et al (2007) found that for male students, a male computer-generated voice was more positively evaluated, trusted, and led to higher confidence levels than a female computer-generated voice.…”
Section: Model-observer Similaritymentioning
confidence: 80%
“…However, findings of Rodicio (2012) and Lee et al (2007) suggest the opposite, namely that male narrations should be preferred. More specifically, Rodicio (2012) found that university students learned more about geology from dynamic visualizations with a male voice-over than a female voice-over, and Lee et al (2007) found that for male students, a male computer-generated voice was more positively evaluated, trusted, and led to higher confidence levels than a female computer-generated voice. Note though, that in these studies, the model was not visible and therefore the cues available to make a social comparison may have been less strong compared to video modeling examples with a visible model (Hoogerheide et al 2014).…”
Section: Model-observer Similaritymentioning
confidence: 89%
See 1 more Smart Citation
“…The similarity attraction hypothesis in the context of learning with animated pedagogical agents would predict increased learning and more positive perceptions the greater the similarity between the learner and the agent. Previous research has explored agent similarity effects with regard to agent gender (Baylor & Kim, 2003;Behrend & Thompson, 2011;Lee, Liao, & Ryu, 2007;Moreno & Flowerday, 2006;Plant et al, 2009;Rosenberg-Kima, Plant, Doerr, & Baylor, 2010;Van der Meij, Van der Meij, & Harmsen, 2012), age (Rosenberg-Kima, Baylor, Plant, & Doerr, 2008) ethnicity (Baylor & Kim, 2003;Behrend & Thompson, 2011;Moreno & Flowerday, 2006;Pratt, Hauser, Ugray, & Patterson, 2007;Rosenberg-Kima et al, 2010), personality (Isbister & Nass, 2000;Moon & Nass, 1998;Nass & Lee, 2001), physical appearance (Rosenberg-Kima et al, 2008;van Vugt et al, 2010), and feedback style (Behrend & Thompson, 2011). Moreno and Flowerday (2006) randomly assigned learners to a choice condition, in which learners selected an agent from 10 options, differing in gender and ethnicity, or a non-choice condition, in which learners were assigned to an agent.…”
Section: Agent Similarity Hypothesismentioning
confidence: 99%
“…Results supported this hypothesis; the two conditions (male and female) with young and 'cool' agents led to higher self-efficacy and interest than the remaining six conditions. Lee et al (2007) explored gender similarity using a computerized voice only. The authors showed that male participants rated a male agent's voice more likeable than a female agent, whereas no difference in voice likeability was found for female participants.…”
Section: Agent Similarity Hypothesismentioning
confidence: 99%